Hysteria: An autoethnographic reflection on making an animated documentary film from archive material. Issue 1 (1st December 2018) - Scott-Hawkins, Alys
This paper investigates the process of collection, interpretation and modification in the making of an experimental animated documentary film. In 2001, I made a two-minute film, Hysteria, as a first year project on the master's animation course at the Royal College of Art. Given as a starting point the word 'bedlam', I researched the history of mental healthcare and discovered documentation of medical practices in the late 1800s of clitoridectomy and genital massage as a 'cure' for the condition of hysteria. Making the film was a singular, insular journey – a stream-of-consciousness voyage of discovery: uncovering and collating material and then interpreting it through visual experimentation. Key to my process was use of a sketchbook that became a space for montage: juxtaposing material from contemporary sources against archive documents and incorporating research material into my visual experiments. Using autoethnographic writing, I return to the state of mind that produced this film – asking how and why it came to exist - and through audio reflection I re-read the sketchbook to analyse the processes of drawing, annotating and editing which produced it. In doing so, I attempt to understand the intuitive process of interpretation, and to draw out insights which can inform my future practice.